Multiple flow rates measurement of exhaled nitric oxide in patients with sarcoidosis: a pilot feasibility study - Choi, J.; Hoffman, L.A.; Sethi, et al., J.M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Fraction of end tidal exhaled nitric oxide (FeNO) has been introduced as a non-invasive marker of airway inflammation in patients with asthma and may have value in monitoring disease activity in patients with sarcoidosis. This pilot study explored: 1) feasibility of the multiple flow rates maneuver to estimate alveolar (CAlvNO) and airway wall ( JAWNO) NO in patients with sarcoidosis; and 2) utility of exhaled NO (FeNO, CAlvNO and JAWNO) measurements to detect and monitor treatment response in patients with active pulmonary sarcoidosis. Patients with sarcoidosis (n=42) and healthy non-smokers (n=20) underwent FeNO measurement at 7 flow-rates (50 to 400 ml/s). Using the Tsoukias and George (1998) model, CAlvNO and JAWNO were estimated. Both patients and healthy non-smokers were able to perform the multiple flow rates maneuver without discomfort, with first measurement success rate of 57% and 65%, respectively. No significant difference was found between patients with sarcoidosis and healthy non-smokers in exhaled NO. None were correlated with pulmonary function tests, except a significant negative correlation between CAlvNO and FVC% (p=0.001) and DLCO% (p=0.012). In 8 patients with active sarcoidosis, FeNO, CAlvNO or JAWNO were not different from those of patients with inactive sarcoidosis.Treatment of active sarcoidosis using oral prednisone and methotrexate did not show any consistent pattern of changes in CAlvNO or JAWNO. Due to a large inter-subject variability and difficulty controlling use of the inhaled corticosteroids, exhaled NO measurement did not appear to be a clinically useful method of monitoring disease progression in sarcoidosis.